2021
DOI: 10.1186/s12955-021-01802-z
|View full text |Cite
|
Sign up to set email alerts
|

Importance of personality and coping expectancy on patient-reported hearing disability, quality of life and distress level: a study of patients referred to an audiology service

Abstract: Purpose According to the World Health Organization (WHO), hearing loss (HL) affects up to 15% of the world’s adult population. Coping and personality are hypothesized to underlie quality of life (QoL) and distress scores. We aimed to study the importance of personality and coping in persons with HL for self-reported hearing disability, QoL, and distress. Methods A cross-sectional survey was carried out, including one hundred and fifty-eight adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“… 31 There is evidence that older adults with HL have a worse quality of life than people without HL. 31 , 35 In the current study, patients in the USER group had a moderately better AQoL-8D score than NON-USERS although the difference was not significant. There was no significant difference in the ‘senses’ subscale of the AQoL-8D questionnaire between the USER and NON-USER groups.…”
Section: Discussioncontrasting
confidence: 54%
“… 31 There is evidence that older adults with HL have a worse quality of life than people without HL. 31 , 35 In the current study, patients in the USER group had a moderately better AQoL-8D score than NON-USERS although the difference was not significant. There was no significant difference in the ‘senses’ subscale of the AQoL-8D questionnaire between the USER and NON-USER groups.…”
Section: Discussioncontrasting
confidence: 54%
“…Consequently also the quality of life of these patients can be impaired. Literatures agree that elderly with hearing loss have a worse quality of life [21,22]. In our study patients in the user group have a trend of better perceived quality of life than non users although differences are not statistically signi cant No differences were observed in the sense subscale of the questionnaire in user and non user subjects.…”
Section: Discussionsupporting
confidence: 39%
“…Patients with severe hearing impairment show a high degree of suffering regarding stress-related disorders compared to those with normal hearing [ 49 ]. Previous research indicated that in hard-of-hearing individuals, the extent of hearing impairment, quality of life, and perceived stress were related to each other and to coping expectations [ 50 ]. The mean proportion of CI patients burdened by higher stress perception measured within this study was 31.6%, a slightly increased but nearly identical proportion to a cross-section of the European population during the COVID-19 pandemic (27.41%) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%